Pengaruh Pembangunan Perumahan Baru Tallasa City Terhadap Lingkungan Hidup: Lokasi Studi : Sepanjang Jalur Lingkar Barat Kelurahan Kapasa Kecamatan Tamalanrea - Hijir Ismail, Muhammad Imam; Syafri; Arief, Rimba (Journal of Urban Planning Studies, 2024)
This study aims to determine the factors that influence the decline in environmental quality caused by the construction of new housing in Tallasa City using Linear Regression Analysis and SWOT Analysis. The variables used consist of 6 (six) variables including (1) Surface Water Conditions, (2) Hydrological Conditions, (3) Topographic Conditions, (4) Soil Type Conditions, (5) Land Use, (6) Drainage Conditions. From the results of the analysis used, one of them produces 4 variables that have a significant effect, namely Surface Water Conditions, Hydrological Conditions, Land Use and Drainage Conditions while the other 2 variables have no significant effect.